2020
DOI: 10.9734/cjast/2020/v39i3831092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Carbide Treatment on Ripening Time and Physicochemical Properties of Mango (Mangifera indica L.) Variety “Kent”, Côte d’Ivoire

Abstract: Aims: this study aims to find out appropriate method of application and the optimum dose of calcium carbide required to initiate ripening of mango var. “Kent”. Study Design: The experimental set-up was of a completely randomized design. Place and Duration of Study: This study was performed in the Department of Genetic and Biochemistry, at the Laboratory of Food Biochemistry of University Peleforo Gon Coulibaly, Korhogo, Côte d’Ivoire, May 1, 2020. Methodology: Seventy uniform, mature green an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…This situation causes several biochemical changes, a respiration rate increase, the remodeling of the structural polysaccharides of the cellular wall, and consequently fruit softening (Gill et al, 2017). The fruits analyzed in this study had similar values to those reported by Cissé et al (2020) for the Kent and Côte d'Ivoire varieties (45-50 N). For their part, Aular and Natale (2013) mentioned that fruit texture has a series of internal and external characteristics that depend on environmental and nutrient factors, as well as on the parameters used to program the equipment used for the analysis (texturometers and tools).…”
Section: Skin Firmness/skin Color Correlationsupporting
confidence: 80%
See 1 more Smart Citation
“…This situation causes several biochemical changes, a respiration rate increase, the remodeling of the structural polysaccharides of the cellular wall, and consequently fruit softening (Gill et al, 2017). The fruits analyzed in this study had similar values to those reported by Cissé et al (2020) for the Kent and Côte d'Ivoire varieties (45-50 N). For their part, Aular and Natale (2013) mentioned that fruit texture has a series of internal and external characteristics that depend on environmental and nutrient factors, as well as on the parameters used to program the equipment used for the analysis (texturometers and tools).…”
Section: Skin Firmness/skin Color Correlationsupporting
confidence: 80%
“…The pH values are also similar to those reported by Shafique et al (2006), who recorded 2.5-5.4 pH values for the Fazli, Ashina, Langra, Surjapuri, Khirshapat, Gopalbhog, Kisanbhog, Mohanbhog, Latabombai, and Ranipasand varieties. Cissé et al (2020) Meanwhile, fruit firmness is an important physical parameter that the mango industry frequently seeks. Additionally, it is widely used to determine the ripeness state of the fruit ( Jassi et al, 2019).…”
Section: Skin Firmness/skin Color Correlationmentioning
confidence: 99%